2019
DOI: 10.1515/gps-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the biological synthesis of silver nanoparticles using Penicillium oxalicum GRS-1 and their antimicrobial effects against common food-borne pathogens

Abstract: Biologically synthesized nanoparticles are gaining importance as they offer several advantages, such as the ease with which they can be scaled up, the cost-effectiveness of the process and the green route of production. In this study, silver (Ag) nanoparticles were biosynthesized using the cellular extract of Penicillium oxalicum GRS-1 and then characterized by ultraviolet visible spectroscopy, X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy (TEM) and Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 47 publications
5
26
0
Order By: Relevance
“…Shahzad et al (2019) evaluated the use of 1, 4, 7, and 10 g quantities of Aspergillus fumigatus BTCB10 biomass, observing greater production, smaller size, and better dispersion of the nanoparticles when the synthesis was based on the use of 7 g of biomass. In the work of Rose et al (2019), employing Penicillium oxalicum , greater nanoparticle production was obtained using a higher biomass concentration, which was attributed to greater release of the nitrate reductase enzyme by the mycelium. Saxena et al (2016) observed higher silver nanoparticle production when the amount of Sclerotinia sclerotiorum biomass was increased.…”
Section: Synthesis Mechanismsmentioning
confidence: 99%
“…Shahzad et al (2019) evaluated the use of 1, 4, 7, and 10 g quantities of Aspergillus fumigatus BTCB10 biomass, observing greater production, smaller size, and better dispersion of the nanoparticles when the synthesis was based on the use of 7 g of biomass. In the work of Rose et al (2019), employing Penicillium oxalicum , greater nanoparticle production was obtained using a higher biomass concentration, which was attributed to greater release of the nitrate reductase enzyme by the mycelium. Saxena et al (2016) observed higher silver nanoparticle production when the amount of Sclerotinia sclerotiorum biomass was increased.…”
Section: Synthesis Mechanismsmentioning
confidence: 99%
“…Additionally, incubation of Phanerochaete chrysosporium mycelium with silver nitrate solution produced silver nanoparticles [49]. Korbekandi and colleagues showed the bioreductive production of silver nanoparticles by using Fusarium oxysporum [50].…”
Section: Synthesis/production Based On Fungimentioning
confidence: 99%
“…These techniques utilize plant extracts, which play a role as effective reducing and stabilizing agents for salt ions to form uniform nanoparticles [ 9 , 10 ]. Recent research has demonstrated that the synthetic process of Ag-NPs using leaf extracts such as Polyalthia longifolia, Geranium (Pelargonium graveolens), Eucalyptus citriodora (neelagiri), Ficus benghalensis (marri), and Penicillium oxalicum can produce NPs with average size from 16 to 58 nm [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%